Two new species of the genus Thalerosphyrus Eaton, 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India - Vasanth, M.; Kubendran, T.; Subramanian, K.a.; Babu, R. (Zootaxa, 2025)
Two new species of the genus Thalerosphyrus are described based on larvae collected from India, viz., T. bengalensis Vasanth, Kubendran & Subramanian sp. nov. and T. sartorii Vasanth, Kubendran & Subramanian sp. nov., and these are described based on larvae collected from Tamil Nadu and West Bengal, India. The new species are closely related to T. flowersi and T. meghalayaensis and compared to all known species of the genus Thalerosphyrus from the Oriental region. These new species are strongly distinguished from T. flowersi, as demonstrated by clear photographs of the paratype specimen of the larva. A key to the known species of the genus Thalerosphyrus from India and a distribution map are provided.